Cultural Demands of the Host-Nation: International Student Experience and the Public Diplomacy Consequences - Triana, Benjamin (Journal of International Students, 2015)
Traditional approaches for hosting international students tend to focus on classroom achievement rather than on intercultural exchange and cultural immersion. Such approaches lessen the possibility of successful educational experiences which also hinders public diplomacy. Two case studies are presented that reveal how structural changes at a southeastern university could be modified in order to address the international student experience and 2.) How the international student experience of former Egyptian president Mohamed Morsi illustrates the need for increased emphasis on intercultural exchange due to the likelihood of international students embarking on influential political and private careers.